PENGARUH GAWAI DALAM POLA ASUH ORANG TUA TERHADAP ANAK USIA DINI (Studi Kasus Orang Tua dari Anak Usia 5 Tahun di TKIT Ibu Harapan Kecamatan Bengkalis) - ismail, mufaro'ah; Sumarni, Titin; Sofiani, Ika Kurnia (AL-ISHLAH: Jurnal Pendidikan, 2019)
This study aims to determine the effect of failure in parenting for early childhood and factors that inhibit or support parents in parenting. This research is a correlation study with product moment correlation analysis. The method in this study is to use a case study approach, instruments or tools used to obtain data through the dissemination and filling of questionnaires by parents, direct interviews with parents and documentation as secondary data so that the data obtained is more complete. After going through a fairly long process of data collection, processing and analysis, it can be seen that there are significant effects of gadgets in parenting for early childhood. The presentation was permissive parenting 88.31%, democratic parenting 61.65% and authoritarian parenting 50.04%. With the analysis that the three parenting styles above are influenced by gatget in the process of parenting parents to early childhood but the most strongly influenced are parents with permissive parenting. The factors that hinder parenting are many 5-year-olds who use gadgets, 5-year-olds can already be friends and choose friends, 5-year-olds have their own desires, and global technological developments. The factors that hinder parents in parenting are many 5-year-olds who use gadgets, 5-year-olds can play with friends and choose friends, 5-year-olds have their own desires, and increasingly sophisticated technology. Supporting factors for parents in parenting are good cooperation in the family, having the same commitment, consistency in caring for children, parents providing educational tools in accordance with the age of the child, and parents providing time to play with children. The solutions for parents, children and early childhood education institutions in caring for children should not be affected by gadgets. For parents, it is better to do and multiply positive activities.